2023
DOI: 10.1186/s40545-023-00532-5
|View full text |Cite
|
Sign up to set email alerts
|

Promoting generic drug usage in Japan: correlation between generic drug usage and monthly personal income

Abstract: Background To reduce pharmacy-related medical expenses, it is necessary to cut drug costs, potentially by increasing generic drug usage. This study analyzes the correlation between generic drug usage and monthly personal income by examining prescriptions for individual drugs. Methods We conducted a cross-sectional study based on the data set from the National Database of Health Insurance Claims and Specific Health Checkups of Japan Open Data Japan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In 2020, there were generic drug shortages in Japan owing to manufacturing violence and quality problems caused by several generic pharmaceutical companies [7]. Other factors including the supply-and-demand balance, shortage of ingredients, and management decisions could also contribute to an unstable supply or shortage of generics and biosimilars [26]. Such unstable supply and shortage could cause anxiety in physicians and patients, resulting in the loss of confidence in generics and biosimilars.…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, there were generic drug shortages in Japan owing to manufacturing violence and quality problems caused by several generic pharmaceutical companies [7]. Other factors including the supply-and-demand balance, shortage of ingredients, and management decisions could also contribute to an unstable supply or shortage of generics and biosimilars [26]. Such unstable supply and shortage could cause anxiety in physicians and patients, resulting in the loss of confidence in generics and biosimilars.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study show that the use of generics for drugs with high drug prices is negatively correlated with monthly personal income for both outpatient out-of-hospital and outpatient in-hospital prescriptions. Suzuki et al 32 reported that the proportion of negative correlation coefficients between the usage rate of generic drugs and monthly personal incomes for outpatient out-of-hospital and outpatient in-hospital prescriptions was over 70%, while that for inpatient prescriptions was 46.9%.…”
Section: Discussionmentioning
confidence: 99%
“…The NODJ includes basic summary tables created from medical inpatient claims, medical outpatient claims, diagnosis procedure combination (DPC) claims, dispensing claims, dental inpatient claims, dental outpatient claims, and specific health checkups (Ministry of Health, Labour and Welfare, 2022b ). The NODJ has been used in several studies to identify trends in drugs prescribed by the Japanese insurance system (Mukai et al, 2020 ; Suzuki et al, 2023 ; Tanaka et al, 2022 ; Tanito, 2022 ). Furthermore, Japan enacted the Cancer Registration Promotion Act in 2013, where the registration of diagnosed cancer cases was started in 2016 under the new National Cancer Registry (NCR) system (Ministry of Health.…”
Section: Introductionmentioning
confidence: 99%